Development of a finite element model of supracondylar fractures stabilized with variable stiffness bone plates - Sutherland, Conor J., author; Puttlitz, Christian M., advisor; McGilvray, Kirk, advisor; Easley, Jeremiah, committee member; James, Susan, committee member (Colorado State University. Libraries, 2019)
Approximately 10% of orthopaedic fracture fixation cases lead to non-union, requiring surgical intervention. Inadequate fixation device stiffness, which causes unwanted fracture gap motion, is believed to be one of the largest factor in poor healing as it prevents ideal tissue proliferation in the callus. By altering the thickness of orthopaedic bone plates, it was theorized that the fracture gap micro-mechanics could be controlled and driven towards conditions that accommodate good healing. The first goal of the project was to create computational FEA models of an ovine femoral supracondylar fracture stabilized with a plate of varying thickness. The models were used to investigate the mechanical behavior of the plate and the callus under different physiological loading conditions. The second goal of this study was to validate the computational model with bench-top experiments using an ex-vivo ovine femoral fracture model. To achieve these goals, novel plates were designed and manufactured with different stiffnesses (100%, 85%, and 66% relative stiffness) to be used to treat a femoral supracondylar fracture model in ovine test subjects; both in-vivo and ex-vivo. The FE models were shown to accurately predict the stress/strain mechanics on both bone and plate surfaces. Micromechanics (strain and pressure) predictions in the fracture gap were reported and used to make tissue type proliferation predictions based on previously reported mechanics envelopes corresponding to bone remodeling. The results indicated that changing plate thickness successfully altered the construct stiffness and consequently, the predicted healing tissue type at the fracture site. The FE methods described could help improve patient specific fracture care and reduce non-union rates clinically. However, further in vivo testing is required to validate the clinical significance of the methods described in this thesis.
Keywords: callus; finite element; ovine; femur; bone plate; fracture stabilisation